ASUPAN PROTEIN, ZAT BESI, DAN VITAMIN C DENGAN KEJADIAN ANEMIA PADA MAHASISWI GIZI POLTEKKES KEMENKES ACEH - Nunung Sri Mulyani; Cut Nabila Sadrina (POLTEKKES KEMENKES MANADO, 2021)
Abstract Young women are at higher risk of developing anemia compared to adolescent males because each month is subjected to menstrual cycles and has wrong eating habits such as lack of protein intake, iron intake and vitamin C intake which plays an important role in preventing anemia. The purpose to know the relation of protein intake, iron, and vitamin C with the incidence of anemia in the student college Poltekkes in Aceh Kemenkes. This type of research using Cross sectional method is performed in January 2020 in the Department of Nutrition Poltekkes Kemenkes Aceh. The process of collecting the intake data using a SQ-FFQ questionnaire and calculated with the nutrisurvey software while Hb Using the Easy Touchtool. Then data is processed by testing the statistical Chi-Square. Most of protein intake is adequate 48sample (84,2%),iron intake isdecrease 49 sample (86%),vitamin C is adequate 32 sample (56,1%). There is a significant connection between intake of proteins with the incidence of anemia. While iron and vitamin C with the incidence of anemia has no significant relation. It is expected to student of D-IV Nutrition in Health Polytechnic of Aceh can increase the intake of iron and vitamin C to prevent anemia. Keywords: Protein intake, iron intake, Vitamin C intake, incidence of Anemia